Research on the evaluation of comprehensive efficiency of technological innovation and eco-environment in China. (10th February 2021) - Li, Hongwei; Pang, Sha; Cao, Yucui; Gao, Junhong
Abstract: To investigate the contribution of technology innovation to eco-environment, this paper sets up a comprehensive efficiency evaluation index system of technology innovation and eco-environment. A relational two-stage data envelopment analysis model with output orientation has been built to evaluate the comprehensive efficiency of technology innovation and eco-environment of 28 provinces of China for 2015. The efficiencies of two-sub-stages, technology innovation efficiency, and eco-environment efficiency have been evaluated and analyzed. The result shows that: first, the average of comprehensive efficiency of technology innovation and eco-environment is 0.1535, which indicates a low level. Second, the results of sub-stages show that the average value of technology innovation efficiency is higher than that of eco-environment efficiency. Third, the comprehensive efficiencies of technology innovation and eco-environment of 28 provinces are mostly influenced by their eco-environment efficiencies. Based on these results, corresponding countermeasures are suggested to improve the comprehensive efficiency of technology innovation and eco-environment of China.